Self-Knowledge and Risk in Stratified Medicine. Issue 1 (2nd January 2017) - Hordern, Joshua
Abstract : This article considers why and how self-knowledge is important to communication about risk and behaviour change by arguing for four claims. First, it is doubtful that genetic knowledge should properly be called 'self-knowledge' when its ordinary effects on self-motivation and behaviour change seem so slight. Second, temptations towards a reductionist, fatalist, construal of persons' futures through a 'molecular optic' should be resisted. Third, any plausible effort to change people's behaviour must engage with cultural self-knowledge, values and beliefs, catalysed by the communication of genetic risk. For example, while a Judaeo-Christian notion of self-knowledge is distinctively theological, people's self-knowledge is plural in its insight and sources. Fourth, self-knowledge is found in compassionate, if tense, communion which yields freedom from determinism even amidst suffering. Stratified medicine thus offers a newly precise kind of humanising health care through societal solidarity with the riskiest. However, stratification may also mean that molecularly unstratified, 'B' patients' experience involves accentuated suffering and disappointment, a concern requiring further research.